Structural-phase states and wear resistance of surface formed on steel by surfacing; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Kapralov E. V. Evgenie; Raykov S. V. Sergey; Vaschuk E. S. Ekaterina; Ivanov Yu. F. Yuriy Fedorovich; Budovskikh E. A. Evgenie; Gromov V. E. Victor (2014, 2014)
Title screen